Prioritizing HIV comparative effectiveness trials based on value of information: generic versus brand-name ART in the US. - Pei, Pamela P; Weinstein, Milton C; Li, X Cynthia; Hughes, Michael D; Paltiel, A David; Hou, Taige; Parker, Robert A; Gaynes, Melanie R; Sax, Paul E; Freedberg, Kenneth A; Schackman, Bruce R; Walensky, Rochelle P (HIV clinical trials, 2015)
Value of Information (VOI) analysis examines whether to acquire information before making a decision. We introduced VOI to the HIV audience, using the example of generic antiretroviral therapy (ART) in the US.